2017
DOI: 10.18632/oncotarget.17024
|View full text |Cite
|
Sign up to set email alerts
|

Osthole inhibits bone metastasis of breast cancer

Abstract: Bone is one of the most common sites for breast cancer metastasis, which greatly contributes to patient morbidity and mortality. Osthole, a major extract from Cnidium monnieri (L.), exhibits many biological and pharmacological activities, however, its potential as a therapeutic agent in the treatment of breast cancer bone metastases remain poorly understood. In this study, we set out to investigate whether osthole could inhibit breast cancer metastasis to bone in mice and clarified the potential mechanism of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…In recent years, multiple treatments have been developed for breast cancer, such as local surgical treatment, radiotherapy and chemotherapy, endocrine therapy, molecular targeted treatment, auxiliary treatment of traditional Chinese medicine and so on, which significantly improves the quality of life and prolongs the survival period of patients ( 7 11 ). A large number of clinical data and experimental studies have shown that the adjuvant treatment of breast cancer patients with traditional Chinese medicine can improve the body's metabolism, reduce the toxic and side effects of radiotherapy and chemotherapy, improve the surgical resection rate and endocrine therapy efficacy, and so on ( 12 , 13 ). The development of traditional Chinese medicine plays an important role in reducing the recurrence and metastasis of tumor, prolonging the survival time, and improving the quality of patients' life ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multiple treatments have been developed for breast cancer, such as local surgical treatment, radiotherapy and chemotherapy, endocrine therapy, molecular targeted treatment, auxiliary treatment of traditional Chinese medicine and so on, which significantly improves the quality of life and prolongs the survival period of patients ( 7 11 ). A large number of clinical data and experimental studies have shown that the adjuvant treatment of breast cancer patients with traditional Chinese medicine can improve the body's metabolism, reduce the toxic and side effects of radiotherapy and chemotherapy, improve the surgical resection rate and endocrine therapy efficacy, and so on ( 12 , 13 ). The development of traditional Chinese medicine plays an important role in reducing the recurrence and metastasis of tumor, prolonging the survival time, and improving the quality of patients' life ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Osthole, a natural coumarin extract from the fruit of Cnidium monnieri (L.) [ 21 ], has several beneficial pharmacological properties, such as antiseizure [ 22 ], antiosteoporosis [ 23 ], and antitumour [ 24 ] activities. Recently, studies found that osthole attenuates chronic kidney failure by inhibition of inflammation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effects of osthol in breast cancer, this compound reduces the metastasis of this cancer to the bone marrow. In an in vivo study [ 54 ], the researchers used a mouse model to investigate the preventive effect of osthol against the metastasis of human breast cancer cells to the bone. Results showed that osthol blocked breast cancer cell growth, migration and invasion, along with enhancement of apoptosis of breast cancer cells.…”
Section: Cellular and Molecular Mechanisms Of Anticancer Effects Omentioning
confidence: 99%